Critical Analysis of Healthcare Delivery, Policy Adaptation, and Patient-Centered Innovation - Alseif, Hawraa Abdulmajeed Ahmad; Ozaybi, Raja Mohammed; Bujbarah, Eman Abdullah Hussain; Alharbi, Hamed Shabib Hajb; Alharbi, Abdulrahman Falah Moh,d; Al-Hussain, Jumanah Abduallah Ali; Almarri, Reem Ali; alhussain, Neda mohammed; Albunasir, Fawzi Ibrahim Nasser (Journal of Ecohumanism, 2024)
The delivery of health care is not without problems, including problems in accessibility, quality of care, patient outcomes, and equity. That is a problem we see in healthcare organizations all over the world. Even if much has been invested into medical technology and policy change, it remains hard for health systems to address the heterogeneous requirements of communities. Thus, this paper outlines a critical evaluation of healthcare delivery, policy adaptation, and patient-centered innovation in order to understand how the systems have changed over time to meet the patient’s needs. Some of the areas of focus include the part played by policy in determining the provision of services, an analysis of patient-centered care, and the part played by technology in the delivery of services. It is also important to emphasize the problems of health care systems of developed and, especially, developing countries concerning disparities and inequality, underfunding, and inefficiency. The paper, based on the consideration of global health reports, different cases, and interviews with experts, aims to disclose how healthcare can meet new patient requirements and simultaneously enhance the result.